ANALYSIS OF THE SUITABILITY OF APPLYING WAKALAH BIL UJRAH FINANCING AGREEMENTS WITH DSN-MUI FATWAS AT BMT EKA MANDIRI MERTOYUDAN - Istighosah, Nurul; Aini, Qurotul; Muhibin, Ahmad (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
One of the supporting contracts used by BMT is the wakalah contract, but in practice there are still differences in implementation and application that are not in accordance with sharia. This causes a discrepancy between the contract in practice and in theory. This study aims to analyze the suitability of the application of the wakalah bil ujrah financing contract with the DSN-MUI Fatwa at BMT Eka Mandiri Mertoyudan. This study uses a descriptive qualitative approach. Primary data was obtained from interviews, observations, and documentation. Interviews were conducted with the Chairman of the Management, Tellers, Administrators, Marketing, and customers. The collected data will be analyzed to obtain relevant results. The results of the study indicate that the wakalah bil ujrah contract at BMT Eka Mandiri Mertoyudan in its practical application does not yet comply with sharia rules and is not in accordance with the DSN MUI fatwa. The wakalah bil ujrah contract is used to conduct transactions on behalf of customers, not to provide funds directly to customers. In practice, there are still obstacles that need to be overcome, such as delays in customer installment payments and limited witnesses in the implementation of the contract from the BMT. In order for the contract to be implemented properly, the BMT needs to review the implementation of the wakalah bil ujrah contract so that it complies with sharia principles and ensures that this contract functions as intended.